2007
DOI: 10.1001/archinte.167.15.1593
|View full text |Cite
|
Sign up to set email alerts
|

Association of Laboratory-Defined Aspirin Resistance With a Higher Risk of Recurrent Cardiovascular Events

Abstract: Background: The risk of recurrence of cardiovascular events among patients using aspirin (acetylsalicylic acid) for secondary prevention of such events remains high. Persistent platelet reactivity despite aspirin therapy, a laboratory-defined phenomenon called aspirin resistance (hereinafter, laboratory aspirin resistance), might explain this in part, but its actual contribution to the risk remains unclear. The objective of this study was to systematically review all available evidence on whether laboratory as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
277
2
12

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 392 publications
(305 citation statements)
references
References 37 publications
14
277
2
12
Order By: Relevance
“…In the present meta-analysis we confirm the data recently published by Snoep et al [7], by systematically analysing all the published clinical studies that evaluated platelet function among patients with CHD on ASA therapy. This in order to give further insights on this matter that is arousing increasing clinical interest among physicians and researchers.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…In the present meta-analysis we confirm the data recently published by Snoep et al [7], by systematically analysing all the published clinical studies that evaluated platelet function among patients with CHD on ASA therapy. This in order to give further insights on this matter that is arousing increasing clinical interest among physicians and researchers.…”
Section: Discussionsupporting
confidence: 87%
“…In a recent systematic review of all the clinical trials that evaluated persistent platelet reactivity in patients under ASA therapy, the mean prevalence of RPR was nearly 25% [3]. Some clinical prospective studies reported a significant association between RPR and the occurrence of secondary cardiovascular events [4][5][6], and a recent meta-analysis by Snoep et al [7] reported a significant role for the laboratory-defined aspirin resistance on the risk of clinical cardiovascular recurrences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…39 However, if "resistance" is defined in pharmacological terms as the failure of aspirin intake to fully inactivate its target, platelet COX-1, as evidenced by lack of inhibition of thromboxane B 2 generation, then aspirin resistance is either a very rare phenomenon [40][41][42] or does not exist. 17 Based on this pharmacologic definition, a study of 400 healthy volunteers failed to identify a single case of aspirin resistance.…”
Section: 34-37mentioning
confidence: 99%
“…Several studies report a link between CT and occurrence of ischaemic events. Meta-analyses comparing patients who are responsive to aspirin treatment and patients with persistent platelet activity despite aspirin therapy suggest that the latter group faces a significantly (Krasopoulos et al: nearly 4-fold) greater risk of adverse CV events (35,(43)(44)(45). Another meta-analysis, based only on prospective studies, shows that high residual platelet reactivity in aspirin-treated CV patients evaluated by the PFA-100 is associated with recurrent ischaemic events (46).…”
Section: Platelet Function Testing In Acsmentioning
confidence: 99%